Survivors of the Shoah: Interviewee: George Soros Part I (United States : Survivors of the Shoah Visual History Foundation, 2000)
Interview with George Soros. The tape is part of a collection of 10 interviews provided to OSA by the Survivors of the Shoah Visual History Foundation. Interviewer: Luca Illy.
Shoah Foundation interview code: 51330
Duration: 01:58:00
Keywords: Documentary films